Monitoring Tool for Electricity Usage in Residential Homes Based on the Internet of Things (IoT) Using BLYNK Application - Nofiansah; Marniati, Yessi; Rumiasih; Yahya, Sudirman; Yani, Herman; Bofynna, Pio Agma (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Electricity is a basic need of human beings. The consumption of electricity usage is getting bigger and bigger. Electricity usage is usually wasteful due to lack of public awareness and ineffective use of electricity. With this problem, the author aims to design loT-based electric power usage monitoring system in home electrical appliances. This tool is designed using sensors to detect the value of the voltage and current of the load attached to the electricity but still using the BLYNK application as a server and application to monitor the use of electric power through a smartphone application. The measurement results include the data of current, voltage, and electrical power used. This system can also remotely switch appliances ON/OFF. The test was conducted by comparing the results of the power value from the power meter with the power value in BLYNK application. After the test, the results of the comparison between the monitoring tool and the power meter measuring instrument obtained an average power error value of 0.5%. So that the accuracy value of the tool can also be 99.5%. With a large accuracy value, it means that the tool works well and can be used to monitor the use of electrical energy in households.